Microstructural and mechanical optimization of selective laser melted Ti6Al4V lattices: Effect of hot isostatic pressing. (May 2022) - Yan, Xingchen; Yue, Shujun; Ge, Jinguo; Chen, Chaoyue; Lupoi, Rocco; Yin, Shuo
Abstract: Ti6Al4V triply periodic minimal surface (TPMS) and Trabecular (Trab.) lattices were manufactured by selective laser melting (SLM). The defect distribution, phase composition, microstructural evolution and mechanical properties after hot isostatic pressing (HIPing) treatment were investigated. For both lattices, only micro-sized pores could be observed without any other defects. HIPing treatment had limited influence on pore elimination when the pore diameters were larger than 30 μm. The as-fabricated acicular martensites were in-situ decomposed into the homogeneous basket-weave α + β structure during HIPing process, and the microstructural anisotropy was effectively eliminated after HIPing. The two lattices had similar α/β phase fraction, but the average grain size of the TPMS lattice (2.206 μm) was much smaller than that of the Trab. One, which was attributed to the original microstructural difference in their as-fabricated counterparts. The compressive strength of the two lattices had no significant change after HIPing treatment, but the energy absorption capacity significantly improved due to the transformation induced plasticity effect of α + β laths formation. The fracture mechanism was altered from the brittle-dominated quasi-cleavage mode to ductility-dominated mode. The findings in this work provide an approach for microstructure and compression ductility improvement of SLM Ti6Al4V porous structure by specific heating treatments.